Study of psychiatric morbidity of patients attending free mental health check up camps in far western rural Nepal - Sedain, C P (Journal of Chitwan Medical College, 2017)
The hilly area of far western development region is the most remote area of Nepal. This is the region of less health facility. The aim of the study was to find out psychiatric morbidity of patients attending free check up clinic of far western development region Nepal. A prospective cross-sectional study comprised of all consecutive patients attending free check up psychiatric clinic of far western development region Nepal. All the patients attending the free clinics for four days were taken as case. The study was performed in the month of June, 2013. Demographic data and disease profile of 287 patients attending the clinic were analyzed. The ratios and proportions were used for statistical analysis. Most of Patients attended of far western development region free mental health clinic were farmer of age group 20-29 years. The commonest incidence of psychiatric illness was depressive disorder and (tension/migraine) headache.